Effect of flaxseed polyphenols on physical stability and oxidative stability of flaxseed oil-in-water nanoemulsions. (15th December 2019) - Cheng, Chen; Yu, Xiao; McClements, David Julian; Huang, Qingde; Tang, Hu; Yu, Kun; Xiang, Xia; Chen, Peng; Wang, Xintian; Deng, Qianchun
Graphical abstract: Highlights: Flaxseed polyphenols exerted differential antioxidant effects in nanoemulsion. SECO and flaxseed lignan macromolecule inhibited lipid oxidation in nanoemulsion. The mechanism mainly related to the partitioning of polyphenols in nanoemulsion. The glucoside in phenolic extracts decreased their association with lipid droplets. Abstract: Recent studies have shown that the high susceptibility of flaxseed oil nanoemulsions to lipid oxidation limits their incorporation into functional foods and beverages. For this reason, the impact of various flaxseed phenolic extracts on the physical and oxidative stability of flaxseed oil nanoemulsions was investigated. Flaxseed lignan extract (FLE) and secoisolariciresinol (SECO) exhibited antioxidant activity whereas secoisolariciresinol diglucoside (SDG) and p -coumaric acid (CouA) exhibited prooxidant activity in the flaxseed oil nanoemulsions. The antioxidant potential of flaxseed phenolics in the nanoemulsions was as follows: SECO < CouA < SDG ≈ FLE. Moreover, the antioxidant/prooxidant activity of the phenolics was also related to their free radical scavenging activity and partitioning in the nanoemulsions. Our results suggested that both SECO and FLE were good plant-based antioxidants for improving the stability of flaxseed oil nanoemulsions.